Efficacy and safety of intravenous mesenchymal stem cells for ischemic stroke patients, a systematic review and meta-analysis - Hassanein, Maged Elsayed; Fayad, Jaber; Shabana, Jilan Ali; AlEdani, Esraa M.; Hefnawy, Mahmoud Tarek; Ghaith, Hazem S.; Negida, Ahmed (Frontiers in Stroke, 2024)
Background Clinical trials have evaluated the efficacy of intravenous mesenchymal stem cells (MSCs) for acute and subacute ischemic stroke. Therefore, we conducted this meta-analysis to investigate the efficacy and safety of intravenous MSC treatments compared to placebo for acute and subacute ischemic stroke patients. Methods We searched PubMed, SCOPUS, Web of Science, and Cochrane CENTRAL for randomized controlled trials evaluating any clinical trials of intravenous MSCs for acute and subacute ischemic stroke patients. The efficacy outcomes of this study were the rates of improvement in National Institutes of Health Stroke Scale (NIHSS) scores, good scores on the modified Rankin Scale (mRS), and Barthel Index (BI) scores, while the safety outcomes were the rates of mortality and stroke recurrence. We compared intravenous MSC and placebo treatments on a fixed-effect meta-analysis model in R software. Results Four randomized controlled studies involving 97 patients were included in the analysis. In the meta-analysis, MSC treatments were superior to placebo treatments in good mRS (MD −0.95, 95% CI [−1.39, −0.52]) or BI (MD 21.36, 95% CI [9.96, 32.75]) scores, and MSC treatments were not superior to placebo treatments in the rate of improvement of the NIHSS scores (MD −1.81, 95% CI [−4.123, 0.494]). MSCs were associated with neither decreased mortality nor stroke recurrence (risk ratio 0.58 and 0.59, respectively; p-value = 0.51 and p-value = 0.533, respectively). Conclusion For patients with acute and subacute ischemic stroke who are eligible for further damage to neural tissue, MSCs achieve high efficacy and acceptable safety. Systematic review registration Prospero, unique ID: CRD42023457655.